Pelaksanaan Pembinaan Terhadap Narapidana di Lembaga Pemasyarakatan Kelas IIA Pematang Siantar - Kesita Eva Lestina Lumban Tobing; Madiasa Ablisar; Muhammad Hamdan; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract. The penal system adopted by Indonesia is regulated in the act invite N0.12 of 1995, this is implementation of imprisonment, which is a philosophical juridical changes of the prison system into a system. The system of increation emphasizes the element revenge and deterrence are gradually seen as something  systems and facilities that are not in line with the concept of rehabilitation and social reintegration and constitutes absorption and an inseparable part of values  contained in Pancasila and the 1945 constitution, from the result of the study showed that arrangement of training programs for prisoners in class IIA Pematangsiantar. Participants in the construction program are under construction personality and independence in the implementation has not been implemented optimally caused by several things, namely there is no separation construction of gender, age, type of crime, long sentence up not in accordance with the objectives of coaching, then the quality of human resources, number of construction workers, constructions budgets, and facilities  and facilities nt yet available adequate, for this reason, this is recommended that Pematangsiantar Class IIA penitentiary be recommended  to further enhance human resources for officers I employees the penitentiary with a variety of trainings, as well perform the construction in accordance with the rules in place.   Keywords: penal system, Coaching, inmate